2020
DOI: 10.2147/cmar.s267825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognosis of Intravascular Large B Cell Lymphoma (IVLBCL): Analysis of 182 Patients from Global Case Series</p>

Abstract: Purpose This study provides an overview of the prognosis of intravascular large B cell lymphoma (IVLBCL) over the past 10 years and analyzes the possible relevant factors. Patients and Methods We conducted a literature search of case reports, case series, and retrospective studies of IVLBCL published from January 2008 to July 2018. After excluding inappropriate data, 103 publications were selected for the analysis. Statistical analyses of different treatment modalities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…A global case series reported that the median patient age of IVLBCL was 64 ± 12.7 years, and that 51.1% of patients were men. 5 The patient described in the present case was 32 years old, which is much younger than the average age of illness. Two recent case series within China reported an average age of onset of 56 6 and 58.5 7 years, suggesting a lower age of onset in China compared with other countries.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A global case series reported that the median patient age of IVLBCL was 64 ± 12.7 years, and that 51.1% of patients were men. 5 The patient described in the present case was 32 years old, which is much younger than the average age of illness. Two recent case series within China reported an average age of onset of 56 6 and 58.5 7 years, suggesting a lower age of onset in China compared with other countries.…”
Section: Discussionmentioning
confidence: 76%
“…IVLBCL generally has a poor prognosis, with 1- and 3-year overall survival rates of 42.3% and 11.5%, respectively. 5 It has naturally highly aggressive and infiltrative tumors and a poor response to chemotherapy. Furthermore, delays in diagnosis are common because of a lack of understanding of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Among the many clinical presentations of IVLBCL, B symptoms are a common manifestation, occurring in 54-76% of patients. [4][5][6] Although the prognosis of IVLBCL is poor due to the frequent delay in early diagnosis, random skin biopsy (RSB) and BM biopsy (BMB) have improved the accuracy of diagnosis, resulting in the prompt initiation of chemotherapy and improved outcomes. 1,3,5,6 However, the results, including flow cytometry and pathological findings of these samples, are often unhelpful in making a diagnosis.We present the case of a patient with IVLBCL resulting in mass formation in the trigeminal nerve (TN).…”
mentioning
confidence: 99%
“…[4][5][6] Although the prognosis of IVLBCL is poor due to the frequent delay in early diagnosis, random skin biopsy (RSB) and BM biopsy (BMB) have improved the accuracy of diagnosis, resulting in the prompt initiation of chemotherapy and improved outcomes. 1,3,5,6 However, the results, including flow cytometry and pathological findings of these samples, are often unhelpful in making a diagnosis.We present the case of a patient with IVLBCL resulting in mass formation in the trigeminal nerve (TN). This case had concurrent abnormal clinical manifestations, such as failure to detect IVLBCL by RSB and BMB, resulting in death due to rapid deterioration.…”
mentioning
confidence: 99%
See 1 more Smart Citation